Home range and activity patterns of Conepatus semistriatus (Carnivora, Mephitidae) in Emas National Park, Brazil - Alfaro, Luis Diego (2014)
Skunks (Mephitidae) have not been well studied throughout the Neotropics. In Brazil there is a general lack of data on the ecology, behavior, distribution, systematics, morphology and biogeographic patterns of the two species occurring in the country (Conepatus semistriatus and C. chinga). The focus of this study was on understanding the home range and activity patterns of C. semistriatus. Field research was conducted in the Emas National Park, where three skunks with radio-collars were located on 157 separate occasions. The observed patterns of activity indicate that the species is predominantly nocturnal, with a great expenditure of time on foraging. Temperature had a direct influence on the animal's behavior, but there was no apparent influence of light on activity patterns. Average home range areas were 1.39 ± 0.87 km2 (Minimum Convex Polygon method) and 0.69 ± 0.25 km 2 (Local Convex Hull method). There was high home range overlap between individuals, 0.27 km2 based on the Minimum Convex Polygon method, at sites with easy access to resources.